Religion and Aesthetic Experience Drama - Sermons - Literature - Dorpmüller, Sabine; Scholz, Jan; Stille, Max; Weinrich , Ines (Heidelberg Studies on Transculturality, 2018)
Religious aesthetics have gained increasing importance over the past few years in the fields of Religious studies and Islamic studies. This volume highlights the transcultural dimensions of the theoretical foundations of religious aesthetics. It explores aesthetic experience in the religious field through a series of case studies. These include Islamic sermons from the Middle East and South Asia, Islamic religious chanting, a chapter of the Qurʾān, a German performance artist, Indian rasa theory, and Arabic and Bengali literature. Together, the authors demonstrate that the analysis of the aesthetic forms of religious mediation across regions and genres is a fruitful approach to transcultural studies.